Clinical and Epidemiological Profile of Otorhinolaryngology Diseases at a Tertiary Hospital in Morang District: A Descriptive Cross-Sectional Study - Bhushan Pandit, Shiva; Shah, Rajeev Kumar; Gyawali, Prakriti (Birat Journal of Health Sciences, 2024)
Introduction: Otorhinolaryngology, dealing with disorders of the ears, nose, throat, and related structures, poses significant health challenges. However, there is a dearth of extensive clinical and epidemiological data on these ailments in the specific geographic area under study. Understanding the characteristics of otorhinolaryngology diseases is crucial for effective healthcare planning and resource allocation.Objective: This study aimed to determine the clinical and epidemiological profile of otorhinolaryngology diseases at a tertiary hospital in Morang District, Nepal.Methodology: An observational descriptive cross-sectional study was conducted at the Otorhinolaryngology department of a tertiary hospital in eastern Nepal from January 15 to February 15, 2024. Data from 600 patients presenting at the department over one month were meticulously analyzed.Results: The median age of patients was 28 years, with the most prevalent age group being 21- 30 years (23%). A majority (56%) were male, and belonged to the Brahmin/Chhetri caste (44.3%). Most patients (85%) initially visited the hospital through OPD, with ear-related issues (35.2%) being the most common complaint. Epistaxis (10.3%) was the most frequent diagnosis, followed by allergic rhinitis (9%) and ear wax issues (8.2%). The prevalence of carcinoma was 12(2%). The majority (77.3%) underwent medical treatment. Outpatient admissions were observed in 68(13.3%) of cases, with emergency admissions accounting for 42(62.6%).Conclusion: Epistaxis, allergic rhinitis, and ear wax problems were commonly encountered. Most patients underwent medical treatment, with only a minority requiring hospital admission, primarily through outpatient services.